The Influence of Self-Efficacy on Students' Mathematical Disposition - Nurma Izzati; Widyastuti Widyastuti (EduMa: Mathematics education learning and teaching, 2021)
This study aims to 1) determine student self-efficacy; 2) Knowing the mathematical disposition of students; and 3) Knowing the effect of self-efficacy on students' mathematical dispositions. The research method uses quantitative methods with a one-shot case study research design. The study population was all students of the Mathematics Tadris Department of IAIN Syekh Nurjati Cirebon in the even semester of the 2020/2021 academic year with the sample being all fourth semester students of the Mathematics Tadris Department of IAIN Sheikh Nurjati Cirebon, namely four classes totaling 151 students. The data collection technique used a questionnaire to determine the students' self-efficacy and mathematical disposition. The results showed that 1) the average student self-efficacy was 72.86, included in the strong category; 2) The average student's mathematical disposition is 74.42, which is included in the strong category; and 3) Self-efficacy has a significant effect on students' mathematical disposition. Self-efficacy has an effect of 68% on students' mathematical dispositionsÂ